106k views
0 votes
Solve the equation.

6(n-4) =3n

2 Answers

3 votes

6(n-4) =3n

mutiply the bracket by 6

(6)(n)(6)(-4)= 3n

6n-24= 3n

Move -24 to the other side. Sign changes from -24 to 24

6n-24+24=3n+24

6n= 3n+24

Move 3n to the other side. Sign changes from +3n to -3n.

6n-3n= 3n-3n+24

6n-3n= 24

3n= 24

divide by 3

3n/3= 24/3

n= 8

Answer: n= 8

User Lasitha Konara
by
4.5k points
1 vote

Answer:

n=8

Explanation:

6(n-4) =3n

apply distributive property:

6*n-6*4=3n

6n-3n=24

3n=24

n=24/3

n=8

User Amit Deshpande
by
4.8k points